Ursodeoxycholic Acid Versus Placebo in Women With Intrahepatic Cholestasis of Pregnancy (PITCHES): A Randomized Controlled Trial. Issue 3 (September 2020) - Chappell, L.C.; Bell, J.L.; Smith, A.; Linsell, L.; Juszczak, E.; Dixon, P.H.; Chambers, J.; Hunter, R.; Dorling, J.; Williamson, C.; Thornton, J.G.
Abstract : ( Lancet . 2019;394:849–860) Intrahepatic cholestasis of pregnancy is the most common pregnancy-specific liver disorder and is associated with increased rates of preterm birth, meconium-stained amniotic fluid, neonatal intensive care unit (NICU) admission, and, for women with peak serum bile acid concentrations of ≥100 μmol/L, stillbirth. Ursodeoxycholic acid, a naturally occurring bile acid, is used to treat hepatobiliary disorders in nonpregnant patients and is widely recommended for the treatment of intrahepatic cholestasis of pregnancy. However, there is only a small amount of evidence available supporting its use for this pregnancy disorder. This current trial aimed to investigate whether the use of ursodeoxycholic acid for intrahepatic cholestasis of pregnancy reduced adverse perinatal outcomes, and examined its effects on other short-term maternal and neonatal outcomes.